PESAN MORAL DALAM CERITA UTTARAKĀNDA RAMĀYĀNA (Kajian dalam Perspektif Susila Pendidikan Agama Hindu) - I Dewa Gede Darma Permana (UHN I Gusti Bagus Sugriwa Denpasar, 2021)
Itihāsa is one part of the breadth of Vedic knowledge, which must be learned at the initial stage of learning Vedas. Speaking further about Itihāsa, Itihāsa consists of two great epic literature, namely Ramāyāna and Mahābhārata. So that the initial knowledge that one can learn when studying Itihāsa is the Ramāyāna book. The Ramāyāna book itself is generally composed of 7 parts known as the Sapta Kānda. Then in the resolution section there is the final Kānda section known as Uttarakānda and of course it contains a moral message. Reflecting on this, this research is interested in examining more deeply the story of Uttarakānda Ramāyāna, to find the moral message contained therein in the perspective of Susila's teachings. In this study, several problems were also formulated, namely related to the nature of the Sapta Kānda Ramāyāna, the Uttarakānda Ramāyāna story, and the moral messages contained therein. By using research methods with the type of qualitative research, and literature study and using data analysis from Miles and Huberman. The results of this study indicate that the story of Uttarakānda Ramāyāna contains many moral messages that are useful for life. It is hoped that this research can be an initial provision for someone who is just learning the Vedas, then they can become a better person through the moral message they receive.